Final height in central precocious puberty after long term treatment with a slow release GnRH agonist. Issue 4 (October 1996) - Oostdijk, W; Rikken, B; Schreuder, S; Otten, B; Odink, R; Rouwé, C; Jansen, M; Gerver, W J; Waelkens, J; Drop, S
Abstract : OBJECTIVE: To study the resumption of puberty and the final height achieved in children with central precocious puberty (CPP) treated with the GnRH agonist triptorelin. PATIENTS: 31 girls and five boys with CPP who were treated with triptorelin 3.75 mg intramuscularly every four weeks. Girls were treated for a mean (SD) of 3.4 (1.0) years and were followed up for 4.0 (1.2) years after the treatment was stopped. RESULTS: The rate of bone maturation decreased during treatment and the predicted adult height increased from 158.2 (7.4) cm to 163.9 (7.5) cm at the end of treatment (p < 0.001). When treatment was stopped bone maturation accelerated, resulting in a final height of 161.6 (7.0) cm, which was higher than the predicted adult height at the start of treatment (p < 0.001). Height at the start of treatment was the most important factor positively influencing final height (r = 0.75, p < 0.001). Bone age at cessation of treatment negatively influenced final height (r = -0.52, p = 0.03). A negative correlation between bone age and height increment after discontinuation of treatment was observed (r = -0.85, p = 0.001). Residual growth capacity was optimal when bone age on cessation of treatment was 12 to 12.5 years. Body mass index increased during treatment and remained high on cessation. At final height, the ratio of sitting height to subischial leg length was normal. Menarche occurred at 12.3 (1.1) years, and at a median (range) of 1.1 (0.4 to 2.6) years after treatment was stopped. The ovaries were normal on pelvic ultrasonography. CONCLUSIONS: Treatment of CPP with triptorelin increases final height, with normal body proportions, and seems to increase body mass index. The best results were achieved in girls who were taller at the start of treatment. Puberty was resumed after treatment, without the occurrence of polycystic ovaries.